Reforma el artículo 49 de la ley orgánica electoral referente al proselitismo político a través de medios informáticos y redes sociales - Tinoco Marquez, Christian Manuel (2017)
The rapid advance of science and technology has enabled a huge growth in the world of communications, in our country the social networks are available to at least 70% of the population. This technological progress experienced by the company, is an evolution in the ways of breaking the law, leading to both the diversification of traditional crimes such as the emergence of new illegal acts. This situation has led to a debate on the need to differentiate or not the rest cybercrime and define their treatment within the legal framework. It is therefore important to note that e-crime is any illegal or criminal conduct in its implementation makes use of electronic technology, either as a method, middle or end. Ecuadorian laws provide penalties for offenses committed through a computer, the immense variety of computer crimes under the Penal Code and is punishable Ecuador, they are laying the foundations for a new jurisprudence. Organic Electoral Code of Democracy Act stipulates in Art.49, paragraph 9 among other duties and powers that have the polling stations "Prevent election day electoral propaganda or proselytism done," this prohibition is even extended to election observers, since the relevant part of Art. 180 of the same Code stipulates that such persons shall not under any circumstances make political propaganda of any kind or agitate for associations having political purposes, voter groups, groups of citizens or candidate; and this same law in Article 291, punishable by 50% of the basic remuneration unified person or persons performing or proselytizing campaign on election day; however it turns into statement merely by reason that not being classified as an electoral offense political campaigning through computer media and social networks, in the period that such activity is prohibited by law, being necessary and urgent to incorporate in the third chapter, entitled INFRINGEMENT, PROCEDURE AND PENALTIES Act stated before a provision criminalizing MADE TO POLITICAL PROCELITISMO through computer media and networks SOCIAES, when the law prohibits it, as an electoral INFRINGEMENT, noting also appropriate sanctions the person or persons who commit this offense.